PENGARUH KARAKTERISTIK PENGGUNA MEDIA SOSIAL, E-WOM, KEPERCAYAAN DAN EKUITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN PENGGUNA KERETA API PADA MASA PANDEMIK COVID-19 - Maziyah Fichri; Rojuaniah Rojuaniah (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
In the era of the industrial revolution 4.0, technological developments are growing rapidly, including in this country of Indonesia. Today, there are many technological sophistications that support the dissemination of information. The development of this technology is marked by the internet. One of the information dissemination tools that use technological sophistication is sosial media. e-WOM has an impact on a brand so that people have awareness of the brand. Therefore, e-WOM is one of the important things in consumer purchasing decisions in this digital era which will continue to develop along with technological developments. The purpose of this study was to explore the relationship between personality characteristics, sosial media characteristics and information characteristics on e-WOM, examine the effect of e-WOM on trust, brand awareness and brand image, and determine the effect of trust on brand awareness and brand image. The sample determination technique uses the purposive sampling method, the researcher uses a sample of Jabodetabek residents between the ages of 17 years - 55 years who use trains during the COVID-19 pandemic totaling 250 respondents. Data analysis was carried out by researchers using the Structural Equation Model (SEM). To validate the measurement model, the researcher used confirmatory factor analysis and to identify the characteristics of the sample using frequency analysis. Based on the results of testing the data in this study, it can be concluded that the characteristics of sosial media users consisting of personal characteristics and sosial media characteristics do not have a positive effect on e-WOM, but information characteristics have a positive effect on e-WOM. Then e-WOM has a positive effect on brand trust and awareness, but not on brand image. Furthermore, brand awareness does not have a positive effect on purchasing decisions, however, brand image has a positive influence on purchasing decisions.